Diagnosis of Asbestos-Related Diseases: The Mineralogist and Pathologist's Role in Medicolegal Field. (March 2016) - Capella, Silvana; Bellis, Donata; Belluso, Elena
Abstract : Abstract: Because asbestos diseases represent a complex pattern of legal, social, and political issue, the involvement of the mineralogist and pathologist for a multidisciplinary assessment of its diagnosis helps investigate the relationship between mesothelioma or lung cancer and occupational or environmental asbestos exposure. In the present study, we consider the concentrations of asbestos bodies (ABs) detected by optical microscopy (OM) and scanning electron microscopy (SEM) and the burden of different kinds of mineral fibers (among which is asbestos) identified by SEM combined with an energy dispersive spectrometer (EDS), in 10 lung tissue samples of subjects with occupational and nonoccupational exposure to asbestos. In all subjects with occupational exposure to asbestos, more than 1000 ABs per gram of dry weight were detected both with OM and SEM; this concentration is internationally accepted as suggesting high probability of past occupational exposure to asbestos. In 9 lung samples of the 10 investigated by SEM-EDS different inorganic fibers were found. Asbestos fibers have been identified too, and more than 100, 000 fibers per gram of dry weight were detected in subjects with occupational exposure; this concentration is internationally accepted as suggesting high probability of past occupational exposure to asbestos. Instead, when the ABs burden is low or moderate (such as in subjects with absent or probable asbestos exposure), the correlation between ABs concentration determined by OM and those determined by SEM is lost. Therefore, when the ABs value in OM is borderline, the SEM investigation became essential. Furthermore, the mineralogical analysis by SEM-EDS (identification and quantification of inorganic fibers in general and asbestos in particular) of the fibers detected in the lung tissues is very useful, if not necessary, to complete the pathological diagnosis of asbestos-related malignancies in medicolegal field.